Development and Validation of a Method for the Quantitative Determination of Etoricoxib in Liquid Dosage Form - A. Kh. Amandusova; A. E. Kovalenko; A. V. Morozov; K. R. Savelyeva; T. L. Batalova; O. A. Ostapyuk; L. V. Persanova; T. Yu. Andreevicheva; A. G. Beniashvili; V. N. Shestakov; S. V. Polyakov (Разработка и регистрация лекарственных средств)
Introduction. Etoricoxib is a selective cyclooxygenase (COX-2) inhibitor used for the treatment of acute pain and has anti-inflammatory and analgesic efficacy. Etoricoxib causes fewer complications compared to other non-steroidal anti-inflammatory drugs (NSAIDs). FSI "SID and GP" has developed an ophthalmic liquid dosage form based on etoricoxib. This article proposes a method for determining the content of etoricoxib in a liquid dosage form by high performance liquid chromatography with UV detection.Aim. Development and validation of a method for the quantitative determination of etoricoxib in liquid dosage form.Materials and methods. Eye drops with a concentration of the active substance etoricoxib of 0.05 % were used for the analysis, a standard sample of etoricoxib (Kekule Pharma Limited, India, series ACE-3 WS001/15). Chromatographic separation performed on an Agilent 1220 Infinity II LC high performance liquid chromatograph (Agilent Technologies, USA) equipped with a gradient pump, a column thermostat, and a diode array detector. The analysis carried out on a Kromasil C8 column 250 × 4.6 mm, using acetonitrile and 0.05 M buffer solution of potassium dihydrogen phosphate pH = 4.2 as a mobile phase in a ratio of 46 : 54. The analysis time was 15 minutes at a detection wavelength of 235 nm.Results and discussion. A method for the quantitative determination of etoricoxib in a liquid dosage form developed and validated according to the following indicators: specificity, linearity, accuracy, range, intermediate precision, repeatability.Conclusion. According to the results of validation tests, all of the listed parameters meet the acceptance criteria. The proposed method characterize by high efficiency and specificity.